Robust and Sustained Effect of Ketamine Infusions Coadministered with Conventional Antidepressants in a Patient with Refractory Major Depression - José Manuel Montes; Elena Luján; Fernado Pascual; Jose María Beleña; Jose Luis Perez-Santar; Luis Javier Irastorza; Jerónimo Saiz-Ruiz (Case Reports in Psychiatry)
Antidepressant treatments show low capacity to achieve full clinical remissions. Electroconvulsive therapy is an alternative treatment which has been shown to be more effective but it is not well tolerated and there are concerns regarding its safety. We present the case of a patient with resistant depression and modest and transient response to ECT and who showed a robust and maintained response after six i.v. ketamine (0.5 mg/kg) infusions without withdrawing her antidepressant regimen. Ketamine was very well tolerated. This case illustrates the potential role of ketamine as a booster to standard antidepressants.